MARRIAGE AS THE MAIN INSTITUTION OF THE STATE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article attempts to analyze the role of the institution of marriage in the legal system of the state. This article discusses the problems of family and marriage in a modern rapidly changing society. The article considers the legal aspect of the problems of family and marriage.
Keywords: marriage, family, law, marriage and family relations, state.